PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK DIGITAL PADA MATERI ASAM DAN BASA - Naurin Syafitri; lazulva lazulva (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2026)
Abstract Developing Digital Scrapbook Learning Media on Acid and Base Lesson at the Eleventh Grade of State Senior High School 7 Pekanbaru This research aimed at developing digital scrapbook learning media on Acid and Base lesson for the eleventh-grade students at State Senior High School 7 Pekanbaru. The selection of Acid and Base lesson was based on the complexity and interrelationship of concepts requiring in-depth understanding from students. In the learning process, students tend to be more enthusiastic when using interesting and non-monotonous media, so innovation in learning media is needed to increase student motivation and understanding. It was Research and Development (R&D) with ADDIE development model limited only to the development stage. Interview and questionnaire were the techniques of collecting data. This research was conducted at State Senior High School 7 Pekanbaru. The validation results showed the percentages 80% (quite valid, and could be used with minor revisions) by media experts and 87% (very valid) by material experts, the percentage of practicality test by teachers was 95.2% (very good), and the percentage of student response test was 85% (very good). Based on the validation results obtained, it could be concluded that the digital scrapbook learning media on Acid and Base lesson was valid to be used as a learning medium. Keywords: Acid and Base, Digital Scrapbook, Learning Media   Abstrak Penelitian ini bertujuan untuk mengembangkan media pembelajran scrapbook digital pada materi asam dan basa untuk siswa kelas XI di SMA Negeri 7 Pekanbaru. Pemilihan materi asam dan basa didasarkan pada kompleksitas dan keterkaitan konsep yang memerlukan pemahaman mendalam dari siswa. Dalam proses pembelajaran siswa cenderung lebih semangat ketika menggunakan media yang menarik dan tidak monoton, sehingga inovasi dalam media pembelajaran sangat diperlukan untuk meningkatkan motivasi dan pemahaman siswa. Jenis penelitian yang digunakan adalah Reasearch and Development (R&D) dengan model pengembangan ADDIE yang dibatasi hanya sampai pada tahap development. Teknik yang digunakan dalam pengumpulan data adalah wawancara dan angket. Penelitian ini dilakukan di SMA Negeri 7 Pekanbaru. Hasil validasi oleh ahli media diperoleh persentase 80% (cukup valid dapat digunakan dengan revisi kecil), ahli materi sebesar 87% (sangat valid), uji praktikalitas oleh guru memperoleh persentase 95,2% (sangat baik), dan uji respon peserta didik memperoleh persentase 85% (sangat baik). Berdasarkan hasil validasi yang didapatkan, maka dapat disimpulkan bahwa media pembelajaran scrapbook digital pada materi asam dan basa valid digunakan sebagai media pembelajaran.